2016
DOI: 10.1002/oa.2515
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Linear Enamel Hypoplasia and Social Status in 18th to 19th Century Edo, Japan

Abstract: Linear enamel hypoplasia (LEH) has been utilised in human bioarchaeology as an indicator of growth disturbance during childhood. However, only a few studies have compared populations of different socio‐economic status in the same time period. This study examines the association between the LEH occurrence pattern and social status in the 18th to 19th century populations in Japan. Detailed archaeological studies on burials from the Edo period (1603–1867) excavated in Tokyo have facilitated estimating an individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 41 publications
1
14
2
1
Order By: Relevance
“…Oyamada et al (2012) demonstrated that Edo period females had higher prevalence of LEH than males in Fukuoka, western Japan. Among the 18th-and 19th-century population in Edo, however, no significant difference in LEH prevalence or number of LEHs per individual was found between sexes in any coffin groups (Nakayama, 2016). In this study, no significant difference in the LEH occurrence patterns was found between sexes in any time period or coffin group, and it is unlikely that the variation of sex distribution among different groups had an effect on the comparison of LEH occurrences.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Oyamada et al (2012) demonstrated that Edo period females had higher prevalence of LEH than males in Fukuoka, western Japan. Among the 18th-and 19th-century population in Edo, however, no significant difference in LEH prevalence or number of LEHs per individual was found between sexes in any coffin groups (Nakayama, 2016). In this study, no significant difference in the LEH occurrence patterns was found between sexes in any time period or coffin group, and it is unlikely that the variation of sex distribution among different groups had an effect on the comparison of LEH occurrences.…”
Section: Discussioncontrasting
confidence: 66%
“…An absolute hierarchy of social status was characteristic of the Edo period society, which was established by the beginning of the 18th century (Asao, 1992). It is necessary to consider social status to make an effective comparison between the groups of different time periods, as a previous study revealed that higher-status individuals had fewer LEHs than lower-status individuals in 18th-and 19thcentury Edo (Nakayama, 2016). In the late Edo period, coffin types were closely associated with the social status of the deceased (Matsumoto, 1990;Tanigawa, 1992Tanigawa, , 1993Tanigawa, , 2004.…”
Section: Methodsmentioning
confidence: 99%
“…As we know, its analysis enables a reconstruction of the level of health and, indirectly, also the economic and social status of the examined population. These studies reveal a general tendency that populations living at a high social level show, on average, a lower prevalence of enamel hypoplasia than communities in poor living conditions (e.g., Nakayama 2016, belonging to this individual was as follows (numbered according to FDI 1971): upper second incisor (22), upper first 14and second premolars (15, 25), upper first (26) and second (17) molars, lower first incisor (41), canine (43), both first premolars (44, 34), and first (36), second (37), and third (38, 48) molars (Fig. 2).…”
Section: Methodsmentioning
confidence: 93%
“…Although differentiation of burial structures by social status was not necessarily evident in the earlier Edo period, before the 17th century (Tanigawa, ), a relatively high level of stress markers (Nagaoka & Hirata, ; Sawafuji et al, ; Yamamoto, ) and the location of the Hitotsubashi site within the settlement of the lower status population (Kato, ) suggest that the skeletons found at the Hitotsubashi site belonged to a lower status. A study comparing the prevalence of linear enamel hypoplasia, non‐specific indicators of stress (Katzenberg et al, ; Lewis, ), in the deciduous teeth from the Edo period suggests higher stress levels in people from lower social statuses (Nakayama, ).…”
Section: Methodsmentioning
confidence: 99%